New Waste Material to Enhance the Performance of Grounding System - Nazatul Shiema Moh Nazar; Suresh Thanakodi; Hazuwan Muhammad (Universitas Ahmad Dahlan, 2017)
This paper presents the new waste material to enhance the grounding system application by using Rice Straw Ashes as backfill to reduce the grounding resistance of the grounding system. Due to the importance of the grounding system, this paper discussed the effectiveness of the grounding system after using the additive material. The additive material that used are rice straw ash and bagasse ash. The technique that used in this paper is a vertical type because more economical to install. From the result, it was found that depth of electrode and soil treatment has an impact in reducing the grounding resistance. In addition, Rice Straw ashes provide a better grounding performance comparable to Bagasse ashes.